Uji Efektivitas Dosis Nutrisi Organik Keong Mas Terhadap Karakter Agronomis dan Produksi Selada Merah (Lactuca sativa L var. crispa) Varietas Red Rapid F1 pada Sistem Hidroponik Rakit Apung - Rizka Syaila Ananda; Rommy Andhika Laksono; H.M Yamin Samaullah (Peneliti.net, 2021)
The use of gold snail organic nutrients as plant nutrition, has the potential as an alternative fertilizers to replace AB Mix and can be increase the production of red lettuce in a floating raft hydroponic system. This study can be to determine the effect of giving organic nutrition doses of golden snails that are able to provide agronomic characters and production of Mera lettuce (Lactuca sativa L. var Crispa) Red Rapid F1 variety on a floating raft hydroponic system. The experiment was conducted at a hydroponic experimental garden screen house located at Padjadjaran University, Jatinangor, Sumedang Regency from March to June 2021. The study used a randomized block design, consisting of 6 treatments, repeated 4 times, namely P0 (AB MIX 3 EC), P1 ( Nutrients of golden snail 30 ml/l of water), P2 (Nutrition of golden snails 30 ml/l of water + AB Mix 3 EC), P3 (Nutrition of golden snails 30 ml/l of water + AB Mix 1.5 EC), P4 (Nutrition of golden snails 15 ml/l water + AB Mix 3 EC), P5 ( Nurisi snails mas 15 ml/l water + AB Mix 1.5 EC). Data analysis using analysis of variance and further test LSD ( Least Significant Different) 5% level. The experimental results showed that the treatments of organic nutrition doses of golden snails gave significantly different effects on the average plant height of 7, 14, 21, 28 and 35 days after planting, the average stem diameter was 14, 21, 28 and 35 days after planting, the average area leaves per plant and the average fresh weight per plant, but not significantly different from the average number of leaves 7,14, 21, 28 and 35 DAP. Treatment P4 (Nutrition of golden snail 15 ml/l water + AB Mix 3 EC) gave the highest average fresh weight per red lettuce plant (5,98 g).